The Influence of Online and Traditional Computer Laboratories on Academic Performance of Students - Ismail, A.O.A. (Springer Verlag, 2019)
This paper focuses on online computer laboratories and traditional computer laboratories attempting to improve the academic performance of studentsâ practical skills. It also explores the differences of participants in online computer laboratory compared to traditional stated laboratory. The method used is a laboratory experiment with two groups. The first group uses online computer laboratory on asynchronous communication mode and the second group uses traditional computer laboratory. The results show that there are significant differences between the two groups in an online laboratory compared to traditional laboratory. In addition, the time spent by each group has significant variation in the two different environments. Moreover, the study shows that the online laboratory is better than traditional laboratory in terms of time variation, benefits, accessibility, flexibility, total acquisition, operation, maintenance cost, and achievement performance. In addition, the impact of online laboratory on the studentsâ academic performance is higher than traditional laboratory. Â© 2019, Springer Nature Switzerland AG.